Peran Guru Bimbingan Konseling dan Guru Pendidikan Agama dalam Pengelolaan Kenakalan Remaja di SMA Negeri 1 Ngadirojo Pacitan - Sri Maryuni; Yetty Sarjono; Tjipto Subadi (Manajemen Pendidikan, 2014)
The purpose of this study is to describe the counseling teacher effort in addressing juvenile delinquency anddescribe the efforts of religious education teachers in addressing juvenile delinquency in SMAN 1 Ngadirojo. This study is a qualitative type. The main subject of research is the principal, teachers, and students. The method of collecting data using interviews, observation, and documentation. The results of this study indicate that (1) Teachers Counseling made various efforts to address juvenile delinquency. Such efforts include preventive activities and curative activities. Measures include preventive activities include making personal guidance, coordination with parents, daily monitoring, and also the provision of coaching programs in Monday. Measures include curative activities include cooperation with the police and health centers, conduct home visits, provide spiritual guidance and direction of talent and interest. (2) The teacher of religious education made  various efforts in addressing juvenile delinquency. teachers packed learning activities using the media and methods as well integrates the values  when the national character of the material conveying religious. efforts outside the organized program of learning is habituation, approaching students in private, in coordination with parents, ask students active in Rohis credible form, as well as perform the operation order.